Step
*
of Lemma
common-limit-squeeze
No Annotations
∀a,b,c:ℕ ⟶ ℝ.
((∀n:ℕ. ((a[n] ≤ a[n + 1]) ∧ (a[n + 1] ≤ b[n + 1]) ∧ (b[n + 1] ≤ b[n])))
⇒ lim n→∞.c[n] = r0
⇒ (∀n:ℕ. r0≤b[n] - a[n]≤c[n])
⇒ (∃y:ℝ. (lim n→∞.a[n] = y ∧ lim n→∞.b[n] = y)))
BY
{ (Auto THEN Assert ⌜∃y:ℝ. lim n→∞.a[n] = y⌝⋅) }
1
.....assertion.....
1. a : ℕ ⟶ ℝ
2. b : ℕ ⟶ ℝ
3. c : ℕ ⟶ ℝ
4. ∀n:ℕ. ((a[n] ≤ a[n + 1]) ∧ (a[n + 1] ≤ b[n + 1]) ∧ (b[n + 1] ≤ b[n]))
5. lim n→∞.c[n] = r0
6. ∀n:ℕ. r0≤b[n] - a[n]≤c[n]
⊢ ∃y:ℝ. lim n→∞.a[n] = y
2
1. a : ℕ ⟶ ℝ
2. b : ℕ ⟶ ℝ
3. c : ℕ ⟶ ℝ
4. ∀n:ℕ. ((a[n] ≤ a[n + 1]) ∧ (a[n + 1] ≤ b[n + 1]) ∧ (b[n + 1] ≤ b[n]))
5. lim n→∞.c[n] = r0
6. ∀n:ℕ. r0≤b[n] - a[n]≤c[n]
7. ∃y:ℝ. lim n→∞.a[n] = y
⊢ ∃y:ℝ. (lim n→∞.a[n] = y ∧ lim n→∞.b[n] = y)
Latex:
Latex:
No Annotations
\mforall{}a,b,c:\mBbbN{} {}\mrightarrow{} \mBbbR{}.
((\mforall{}n:\mBbbN{}. ((a[n] \mleq{} a[n + 1]) \mwedge{} (a[n + 1] \mleq{} b[n + 1]) \mwedge{} (b[n + 1] \mleq{} b[n])))
{}\mRightarrow{} lim n\mrightarrow{}\minfty{}.c[n] = r0
{}\mRightarrow{} (\mforall{}n:\mBbbN{}. r0\mleq{}b[n] - a[n]\mleq{}c[n])
{}\mRightarrow{} (\mexists{}y:\mBbbR{}. (lim n\mrightarrow{}\minfty{}.a[n] = y \mwedge{} lim n\mrightarrow{}\minfty{}.b[n] = y)))
By
Latex:
(Auto THEN Assert \mkleeneopen{}\mexists{}y:\mBbbR{}. lim n\mrightarrow{}\minfty{}.a[n] = y\mkleeneclose{}\mcdot{})
Home
Index